2014
DOI: 10.5937/ror1401001z
|View full text |Cite|
|
Sign up to set email alerts
|

Nanomaterials environmental risks and recycling: Actual issues

Abstract: 2 Univerzitet u Beogradu, Institut za hemiju, tehnologiju i metalurgiju, Beograd 3 Institut za tehnologiju nuklearnih i drugih mineralnih sirovina, Beograd 4 Univerzitet u Prištini, Fakultet tehničkih nauka, Kosovska Mitrovica Primljen: 7. april 2014. Prihvaćen: 22. maj 2014.IZVOD -Nanotehnologije se smatraju pokretačkom snagom nove industrijske revolucije. Nanonauka je tokom poslednje decenije značajno evoluirala od nauke koja se isključivo razvijala u laboratorijskim uslovima, do njene aplikacije u primenjen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, these techniques are energy intensive. Alternative methods include the application of molecular antisolvents, pH or thermal responsive materials, and magnetic fields [ 274 ]. In batteries the successful recovery of nanomaterials has already been demonstrated at the benchtop level for nanomaterials such as Zn and ZnO nanoparticles and Graphite-polyaniline nanocomposites via Inert gas condensation (thermal) and vacuum separation, Hydrometallurgy and liquid-liquid extraction, and Oxidative polymerization and Precipitation [ 275 ].…”
Section: Exposure Effects Related To Nanomaterials Life Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these techniques are energy intensive. Alternative methods include the application of molecular antisolvents, pH or thermal responsive materials, and magnetic fields [ 274 ]. In batteries the successful recovery of nanomaterials has already been demonstrated at the benchtop level for nanomaterials such as Zn and ZnO nanoparticles and Graphite-polyaniline nanocomposites via Inert gas condensation (thermal) and vacuum separation, Hydrometallurgy and liquid-liquid extraction, and Oxidative polymerization and Precipitation [ 275 ].…”
Section: Exposure Effects Related To Nanomaterials Life Cyclesmentioning
confidence: 99%
“…In batteries the successful recovery of nanomaterials has already been demonstrated at the benchtop level for nanomaterials such as Zn and ZnO nanoparticles and Graphite-polyaniline nanocomposites via Inert gas condensation (thermal) and vacuum separation, Hydrometallurgy and liquid-liquid extraction, and Oxidative polymerization and Precipitation [ 275 ]. Barriers to the effective recycling and reuse of nanomaterials arise in a lack of guidelines and strategies for the recovery and reuse of nanomaterials [ 274 ]. As researchers and regulatory bodies work to establish practical strategies and guidelines the development of reusable biosensors should be prioritized [ 276 , 277 ].…”
Section: Exposure Effects Related To Nanomaterials Life Cyclesmentioning
confidence: 99%
“…Considering widespread of applications of the constituent elements and their alloys it can be expected that alloys of the AgeBieGa system could be foremost interesting for application in electronics industry. Moreover, numerous studies covering AgeBieX [9e11], AgeGaeX [12,13] and BieGaeX [14,15] systems can be found in literature, as well as more recent studies on similar ternary systems [16e22].…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily because these pollutants are easy to handle in the liquid phase. However, inorganic crystalline pollutants are characterized by low water solubility and a little susceptibility to various biotransformations, thus causing significant difficulties with remediation processes, with little progress in the field 22 26 . Consequently, discovering green solutions for remediating nanomaterials remains a challenging and underexplored field.…”
Section: Introductionmentioning
confidence: 99%